Analysis of the spatiotemporal characteristics of drought disasters in North China during the Ming and Qing dynasties. Issue 1 (13th November 2020) - Bi, Shuoben; Bi, Shengjie; Chen, Changchun; Lu, Ying; Nkunzimana, Athanase; Li, Yanping
Abstract: The present study sought to understand the spatiotemporal characteristics, associated with changes in drought disasters during the Ming and Qing Dynasties in North China. The grade sequence of drought disasters at 21 sites for the given period (1470–1912 AD) in North China was studied herein. An ensemble empirical mode decomposition (EEMD) was used to analyze the multiple time-scales towards generating a simple and stable intrinsic modal function component. Comparisons and analysis of the frequency and intensity of drought disasters were made using polynomial fitting curves to understand the temporal variations of drought disasters. Two aspects were explored to study the spatial distribution and characteristics of drought disasters. The reconstruction of the sequence of drought disasters was based on the Empirical Orthogonal Function (EOF) and Rotated Empiric Orthogonal Function (REOF). The drought disaster was divided into several space modes and sensitive areas. Drought frequency was recurrent in the northern and low in the southern part of North China. Findings revealed drought frequency and intensity were high in southeast and low in the southwestern part of North China. The study would inform decisions on disaster prevention and mitigation thereby serving as a baseline print for predicting modern drought disasters.